PENERAPAN MEDIA ULAR TANGGA TANGGA UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS IV SDN POJOKSARI 1 - Kemal, Vina; Hafizh, Muhammad (Jurnal PGSD Indonesia, 2023)
The low science learning outcomes of class IV students at SDN Pojoksari 1 were the background for conducting this research. Based on the results of observations and test scores for thematic science content lessons, it shows low student learning outcomes. This research is Classroom Action Research which was carried out with the aim of improving class IV science and science learning outcomes at SDN Pojoksari 1 using Snakes and Ladders media. This research will be carried out in 2 cycles. Each cycle in this action consists of four stages, namely planning, implementation, observation and reflection. The subjects in this research were 13 grade IV students at SDN Pojoksari 1. The data collection technique in this research uses a multiple choice test method. Data analysis in this research uses qualitative and quantitative. The research results showed that the average science learning achievement in the pre-cycle was 23.07%, in the first cycle was 69.23% and in the second cycle was 84.61%. Based on the research results, it can be concluded that there was an increase in science and science learning achievement for class IV students at SDN Pojoksari 1 Magetan after learning was carried out using snakes and ladders media